Analysis of Interests Students in Learning Geography in Class XI IIS in MAN 1 Sintang - Putri, Elma Salsabila; Harjanti, Diah Trismi; Buwono, Sri (Jurnal Pendidikan Sosiologi dan Humaniora, 2024)
The objective of this research is to know how the interest of the students to study the subject of geography class XI IIS in MAN 1 Sintang, so that the teacher can find a solution to solve the problems felt by the students in their learning activities, so the students will gain success from their learning. The form of research used in this research is qualitative research with descriptive research methods. Data collection techniques in this study use observation, interview, and documentation methods. The data collection tools used are observation sheets, documentation and interview guidelines. Data analysis uses the Miles and Huberman model that consists of data reduction, data presentation, conclusion drawing. The results of the research showed that students of class XI IIS were interested in geography subjects. Students' interest in learning can be seen through 4 indicators, namely, the feeling of pleasure, the attention of the students, the involvement of students, and the willingness to learn the students. So students are said to be interested in geography subjects because they meet the four indicators of interest in learning.